Interart Translation: A Review, A Definition, and a Critical Assessment - Duygu Tekgül Akın; Aysun Kıran (İstanbul Üniversitesi Çeviribilim Dergisi)
This article proposes the concept of interart translation based on an examination of the relevant literature in the fields of translation studies, literary studies, cultural studies and visual art. Interart translation may be defined as transformations of artistic expression between genres. Examples include theatre or film adaptations of literary works, sculptures inspired by poetry or installation art inspired by music. For the purposes of the paper, interart translation refers to those processes of creative transfer where the point of departure, or source “text,” and the outcome, the target “text,” are works of art in their own right. There is a body of scholarly engagement that explores works of art created through intermedial transpositions from a multiplicity of perspectives. However, to date, they have not been addressed in conjunction with each other and the term “interart translation” remains marginal. The paper outlines contributions to various research traditions and puts them in dialogue with each other. The discussion highlights the relevance of the concept, offering it as an umbrella term to cover phenomena that have hitherto been referred to as intersemiotic translation, adaptation, etc. The article points out the benefit of having a new term in circulation by connecting disparate research avenues.